Inflammation—Cause or consequence of late onset Alzheimer's disease or both? A review of the evidence. (May 2022) - Zhao, Jinrong; Zhao, Dong; Wang, Jinpei; Luo, Xiaoe; Guo, Rui
Accumulating evidence suggests that inflammation is involved in the development of late onset Alzheimer's disease (LOAD). However, it is not clear whether inflammation is a cause or consequence, or both. The aim of this paper is to review the relationship between inflammation and LOAD. We also review the effect of anti-inflammation on the risk of LOAD to further elucidate the relationship between inflammation and LOAD.